Improvement of A5/1 encryption algorithm based on Using Unit Delay - Sattar B. Sadkhan; Nibras Hadi Jawad (Al-Qadisiyah Journal of Pure Science, 2017)
The authentication and the security mechanism are very important in mobile networks because the GSM networks are susceptible to many attacks aiming to penetrate the conversation and access to data transmitted through the network. The GSM security and encryption algorithms are used to provide authentication and radio link privacy to users on GSM network. Encryption algorithm is one of the elements of the GSM networks security where it depends on the encryption algorithm A5/1. A5/1 is strong encryption algorithm used for encryption of conversations on GSM mobile phones. This algorithm in its structure depends on the stream cipher that is very fast, where the sequence key generated must have large period, and good statistical properties. The aim of this paper is to improve GSM network security by improving one of the components of the GSM network security which is A5/1encryption algorithm, with applying (unit delay) to increase length of generated key stream sequence. The Simulation of A5/1 encryption algorithm was implemented in SIMULINK.